In-vitro Characterization of Optimized Multi-Unit Dosage Forms of Theophylline and its Solid State Characterisation - MU Uhumwangho; KV Murthy Ramana (Journal of Applied Sciences and Environmental Management)
The objective of this study is to compare the drug release profile of an optimized multi-unit dose (MU) tablet consisting of rapid and slow release components, a formulated sustained released tablet and two brands of sustained release tablet formulations in the market with a designed model. The fast release component consisted of conventional granules while the slow release component consisted of wax granules of theophylline. The optimized MU tablets was formed by mixing the conventional and matrix granules in ratio 1:1 and compressed. Parameters evaluated were tablet tensile strength and dissolution studies. The optimized formulation was characterized with Differential Scanning Calorimetry and Fourier-Transform Infrared Spectroscopy. Results showed that the optimized MU tablets gave dissolution profile that was comparable with that of the designed model. The following were the dissolution parameters of the optimized MU formulation: the maximum release (m∞) = 91%, prompt release dose (mp) = 24%, time to attain maximum release (t∞) = 12h and first order release rate constant (k) = 0.20 h-1 which is comparable with the release data for the model. The other formulations deviated by giving mp and t∞ that were too low compared with those of the model. There were also no drug/excipient interactions. The indication is that the prompt release dose was determined not only by the amount of the rapid release components in the MU dose formulation but also by the amount of sustained release components, attributable to the deformation of granules of rapid components into that of slow release components during tablet formulation.